New species and barcode analysis of Bethylus Latreille (Hymenoptera, Bethylidae) from South Korea - Kyung Min Lee; Il-kwon Kim; Jongok Lim (ZooKeys)
For the first time, Bethylus Latreille, the type genus of Bethylidae (Hymenoptera, Chrysidoidea, Bethylinae), is reported from the Korean Peninsula based on the discovery of a new species, Bethylus colligatus sp. nov., which was collected in Gangwon Province near the Demilitarized Zone. This new species is described and illustrated. A phylogenetic analysis was conducted using mitochondrial cytochrome c oxidase subunit I sequences from common Bethylus species to better understand the evolutionary relationships within the genus. The resulting phylogeny supports the distinction between B. colligatus sp. nov. and other species. Additionally, a key to the species of Bethylus in East Asia is provided.